ANALISIS CERPEN SEPOTONG SURAT DALAM DIAM KARYA ASMA NADIA MENGGUNAKAN PENDEKATAN OBJEKTIF DAN MIMETIK - Syifani Aryanti; Dzira Auliya Marsela (Populer: Jurnal Penelitian Mahasiswa, 2022)
Literary work is the author's reflection on the reality of life.This study aims to determine the intrinsic and extrinsic elements contained in the short story "a piece of a letter in silence" by Asma Nadia with a mimetic and objective approach. The method used in this research is through a qualitative descriptive analysis with a mimetic approach and objective approach in the work literature. The data analysis technique used is reading and observe short stories, collect data, describe, and drawconclusions from research results. The results of the research show that there are valuesthe reality of life in the form of social reality, the reality of life's struggle, the reality of the real world contained within short story "a letter in silence" with a mimetic approach.The conclusion of this research is that there is a phenomenon of reality values ​​within short story, in the form of the love struggle of a man without a name for a woman without a name even though it has no beautiful ending.